(untitled) (Economic and Political Thought, 2013)
The publication is aimed at demonstrating the political dimension of the discussion on the establishing of the Foundation ‘Flight, Expulsion, Reconciliation’. The article is also an attempt to answer a question about the influence of that debate on the present-day relations between Poland and Germany. The presented polemic over the issue ends at the turn of the years 2009/2010. It was a period when the most important decisions in connection with the shape of the foundation, the German government’s response to the Federation of Expellees’ history interpretation policy, were made. The Act passed by Bundestag created the basis for the establishment of a new institution, was an expression of a wide compromise between the two biggest parliament factions of the Federal Republic (CDU/CSU and SPD) and depicted the actual powers in the German parliament. The unquestionable success of Bund der Vertriebenen (BdV) was the fact that, in spite of the long-lasting opposition, especially on the part of Polish politicians, the Foundation Board has six seats for the members of BdV as a compensation for the Federation of Expellees’ Chairperson’s resignation to be a member of that body. This way the representatives of the German expellees gained an opportunity to have a direct influence on the future conception of the museum, although to a limited extent. The author, with the use of a comparative method, analyzes the stands of particular representatives of the German political parties on that issue. Due to the topicality of the issue, press publications are the main sources. Source materials in the German language, including the Bundestag plenary sessions protocols and the Federation of Expellees’ press releases, also played an important role.